MARKAS SEKTOR PEMADAM KEBAKARAN DI BANJARMASIN - Halim, Muhammad; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Beside being known as the City of Thousand Rivers, Banjarmasin is also known as the “City of a Thousand Fire Fighters. It has a large number of fire station, especially from the local community. However, this creates new problems of uncontrolled fire extinguishers and lack of efficiency and effectiveness in their work. According from this, it felt necessary to encourage the government to improve their performances of the fire station. Design use universal architecture method to get a modular design and could be built in wherever place, especially at fire-prone area. The result is a fire department that can satisfy needs and provide of users in the aspects of service, education and controlling based on the area division.